Automatic metric 3D surface mesh generation using subdivision surface geometrical model. Part 2 : mesh generation algorithm and examples - Lee, Chi King (2014)
In this paper, a new metric advancing front surface mesh generation scheme is suggested. This new surface mesh generator is based on a new geometrical model employing the interpolating subdivision surface concept. The target surfaces to be meshed are represented implicitly by interpolating subdivision surfaces which allow the presence of various sharp and discontinuous features in the underlying geometrical model. While the main generation steps of the new generator are based on a robust metric surface triangulation kernel developed previously, a number of specially designed algorithms are developed in order to combine the existing metric advancing front algorithm with the new geometrical model. As a result, the application areas of the new mesh generator are largely extended and can be used to handle problems involving extensive changes in domain geometry. Numerical experience done indicates that, by using the proposed mesh generation scheme, high quality surface meshes with rapid varying element size and anisotropic characteristics can be generated in a short time by using a low -end PC. Finally, by using the pseudo-curvature element-size controlling metric to impose the curvature element-size requirement in an implicit manner, the new mesh generation procedure can also generated finite element meshes with high fidelity to approximate the target surfaces accurately.